ANALISIS PENGGUNAANACTIVITY BASED COSTING(ABC) UNTUK MENENTUKAN HARGA POKOK PRODUK DAN HARGA JUAL PADA KEDAI ROTI MAROS TIMIKA - Murnitasari .; Ahmad Tomu (JURNAL ULET (Utility, Earning and Tax), 2019)
This study aims to determine the cost of products using the activity based costing method and to find out the selling price of the product on the basis of determining the cost of production using the activity based costing method at the Maros Bakery. The method used in this research is descriptive analysis method. The analytical tool used was calculating the cost of production and calculating the selling price. From the results of the study it can be concluded that the cost of production and selling prices use a higher activity based costing method other than the original flavored bread product. This is because the burden of overhead on each product is charged to several cost drivers so that this method is able to allocate activity costs to each product precisely based on the consumption of each activity.